Strange Blood : the Rise and Fall of Lamb Blood Transfusion in 19th Century Medicine and Beyond - Berner, Boel (Medical humanities (Transcript (Firm)), 2020)
In the mid-1870s, the experimental therapy of lamb blood transfusion spread like an epidemic across Europe and the USA. Doctors tried to use it as a cure for tuberculosis, pellagra, and anemia; proposed it as a means to reanimate seemingly dead soldiers on the battlefield. It was a contested therapy because it meant crossing boundaries and challenging taboos. The book takes the reader on a unique journey into hospital wards and lunatic asylums, physiological laboratories and 19th century wars. It presents a fascinating story of medical knowledge, ambitions, and concerns - a story that provides valuable lessons for current debates on the morality of medical experimentation and care.